Integrated Very Low Frequency Electromagnetic (Vlf-Em) Geophysical And Hydrogeochemical Study Of Abeku Dumpsite In Ibadan, Southwestern Nigeria - Osinowo Olawale Olakunle; Falufosi Michael Oluseyi; Okafor Austin Ejimunkonye (GeoScience Engineering, 2018)
Very Low Frequency Electromagnetic (VLF-EM) and hydrogeochemical studies have been integrated to measure ground conductivity and also determine the concentration of leachate derived contaminants in the groundwater around Abeku dumpsite in Ibadan, southwest Nigeria. Ten (10) VLFEM profiles were occupied within and around the dumpsite fence. Water sample from wells were also analyzed to determine the concentration of pollutants in the study area. Qualitative interpretations of VLF-EM results indicate relatively high ground conductivity within the dumpsite, which decreases away from the actual waste dump phase of the dumpsite. Ground conductivity is relatively higher in the south and east of the dumpsite which are located downhill of the groundwater hydrostatic head when compared with the north and west of the study area situated uphill of hydraulic gradient. Hydrogeochemical analyses present NO3−, SO42− and PO42− ions concentration in the range of 9.24 – 13.64 mg/L, 3 – 12 mg/L and 0.33 – 1.07 mg/L respectively. The SO42− and PO42− ions concentrations are within permissible limits, while the NO3− ion concentration is slightly above the Federal Ministry of Environment’s standard for potable water in Nigeria.